Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41592-022-01422-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and correcting false transients in calcium imaging

Abstract: Population recordings of calcium activity are a major source of insight into neural function. Large dataset sizes often require automated methods, but automation can introduce errors that are difficult to detect. Here we show that automatic time course estimation can sometimes lead to significant misattribution errors, in which fluorescence is ascribed to the wrong cell. Misattribution arises when the shapes of overlapping cells are imperfectly defined, or when entire cells or processes are not identified, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The least-squares cost enforces a linear-Gaussian data generation hypothesis, however, a number of nonlinearities in fluorescence dynamics, incompleteness in component discovery, and the non-Gaussian statistics of the photo-diodes all contribute to various extents of errors in demixing. Four main alternatives have emerged, including a robust-statistical approach leveraging a Huber cost function, 87 a contamination-aware generative model approach, 92 a zero-Gamma mixture model, 93 and a deep-learning approach. 94…”
Section: Methods Focusing On Space and Timementioning
confidence: 99%
See 4 more Smart Citations
“…The least-squares cost enforces a linear-Gaussian data generation hypothesis, however, a number of nonlinearities in fluorescence dynamics, incompleteness in component discovery, and the non-Gaussian statistics of the photo-diodes all contribute to various extents of errors in demixing. Four main alternatives have emerged, including a robust-statistical approach leveraging a Huber cost function, 87 a contamination-aware generative model approach, 92 a zero-Gamma mixture model, 93 and a deep-learning approach. 94…”
Section: Methods Focusing On Space and Timementioning
confidence: 99%
“…A prime example of such an effect is explored in Ref. 92, in which it is shown that the i.i.d. Gaussian noise assumption often considered can create bleed-through between overlapping cells and additional fluorescent biological processes in the tissue.…”
Section: Validation and Assessmentmentioning
confidence: 99%
See 3 more Smart Citations